Sistem Pendukung Keputusan Menentukan Penerima Beasiswa Kurang Mampu Menggunakan Metode Profile Matching - Agustina Setiyowati; Latifah Ayu Ramadhani; Moh Khoirul Amin (Jurnal Informatika Upgris, 2019)
SMA Masehi 2 PSAK Semarang is a private high school education institution engaged in student affairs that provides several scholarship programs, one of which is underprivileged scholarship programs using KIP (Smart Indonesia Cards). So far, student affairs often experience difficulties in determining students who are eligible to get scholarships and seem subjective in their assessment without considering other requirements so that inequalities arise in the provision of scholarships. Profile Matching was chosen as a method in making the system because it has a profile value that is similar to the standard recipient of the scholarship and allows a decision support system to be built using the Profile Matching method that has criteria such as KIP cards, student grades, parental income, extracurricular and achievement.